Methodical basis of training of cadets for the military applied heptathlon competitions - R.V. Anatskyi; O.E. Kolomiitseva; M. Cretu; V. Potop (Physical Education of Students)
The purpose of the research is to develop methodical bases of training of cadets for the military applied heptathlon competitions. Material and methods: Cadets of 2-3 courses at the age of 19-20 years (n=20) participated in researches. Cadets were selected by the best results of exercises performing included into the program of military applied heptathlon competitions (100 m run, 50 m freestyle swimming, Kalashnikov rifle shooting, pull-up, obstacle course, grenade throwing, 3000 m run). Preparation took place on the basis of training center. All trainings were organized and carried out according to the methodical basics: in a week preparation microcycle five days cadets had two trainings a day (on Saturday was one training, on Sunday they had rest). The selected exercises with individual loads were performed, Results : Sport scores demonstrated top results in the performance of 100 m run, 3000 m run and pull-up. The indices of performing exercise "obstacle course" were much lower than expected. Rather low results were demonstrated in swimming and shooting. Conclusions . Results of researches indicate the necessity of quality improvement: cadets’ weapons proficiency; physical readiness to perform the exercises requiring complex demonstration of all physical qualities.